Unraveling Motivation in English Language Learning: Insights from Non-EFL University Students - Ulfah, Badriyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
Motivation plays a pivotal role in the success of second language acquisition, as indicated by numerous studies. While it has long been acknowledged that motivated learners tend to achieve better outcomes, various taxonomies have emerged to differentiate motivation types. The two widely recognized classifications are intrinsic/extrinsic and integrative/instrumental. This cross-sectional research aims to comprehensively discuss and analyze the four types of motivation exhibited by students at one of the private university in Indonesia enrolled in English for International Communication (TOEIC-based) classes. A structured questionnaire based on Gardner's Attitudes/Motivation Test Battery (AMTB) was utilized as the research instrument. The study spanned one year, during which students were exposed to a minimum of two TOEIC-based classes. The research sample, consisting of 446 students, was thoughtfully selected through purposive sampling techniques. This sample was further stratified, with 254 students drawn from the third-fourth semesters and 192 students from the fifth-sixth semesters. The findings, presented in numerical format, revealed that a majority of students demonstrated high levels of motivation across all motivation classifications. This research sheds light on the motivation dynamics of the students, providing valuable insights for educators and language learning practitioners.